Schisandrin B Induced ROS-Mediated Autophagy and Th1/Th2 Imbalance via Selenoproteins in Hepa1-6 Cells - Tan, Siran; Zheng, Zhi; Liu, Tianqi; Yao, Xiaoyun; Yu, Miao; Ji, Yubin (Frontiers in Immunology, 2022)
Schisandrin B (Sch B) is well-known for its antitumor effect; however, its underlying mechanism remains confusing. Our study aimed to investigate the role of selenoproteins in Sch B-induced autophagy and Th1/Th2 imbalance in Hepa1-6 cells. Hepa1-6 cells were chosen to explore the antitumor mechanism and were treated with 0, 25, 50, and 100 μM of Sch B for 24 h, respectively. We detected the inhibition rate of proliferation, transmission electron microscopy (TEM), monodansylcadaverine (MDC) staining, reactive oxygen species (ROS) level and oxidative stress-related indicators, autophagy-related genes, related Th1/Th2 cytokines, and selenoprotein mRNA expression. Moreover, the heat map, principal component analysis (PCA), and correlation analysis were used for further bioinformatics analysis. The results revealed that Sch B exhibited well-inhibited effects on Hepa1-6 cells. Subsequently, under Sch B treatment, typical autophagy characteristics were increasingly apparent, and the level of punctate MDC staining enhanced and regulated the autophagy-related genes. Overall, Sch B induced autophagy in Hepa1-6 cells. In addition, Sch B-promoted ROS accumulation eventually triggered autophagy initiation. Results of Th1 and Th2 cytokine mRNA expression indicated that Th1/Th2 immune imbalance was observed by Sch B treatment in Hepa1-6 cells. Intriguingly, Sch B downregulated the majority of selenoprotein expression. Also, the heat map results observed significant variation of autophagy-related genes, related Th1/Th2 cytokines, and selenoprotein expression in response to Sch B treatment. PCA outcome suggested the key role of Txnrd1, Txnrd3, Selp, GPX2, Dio3, and Selr with its potential interactions in ROS-mediated autophagy and Th1/Th2 imbalance of Hepa1-6 cells. In conclusion, Sch B induced ROS-mediated autophagy and Th1/Th2 imbalance in Hepa1-6 cells. More importantly, the majority of selenoproteins were intimately involved in the process of autophagy and Th1/Th2 imbalance, Txnrd3, Selp, GPX2, Dio3, and Selr had considerable impacts on the process.